No coração da cracolândia da Luz: entre horrores, amores e resistência - Dotta, Beatris Guarita (2021)
Aiming to understand how the relationships between the different actors that make up Cracolândia occur, this research starts from the experiences of the researcher in the field and dialogues with multiple sources and authors. A Field Diary was used to record what was experienced in Cracolândia da Luz through the Pastoral do Povo de Rua. The relationships between people living on the streets, public authorities, police force and social movement volunteers are narrated here. We expand this narrative by dialoguing with Michel Foucault, about control policies; and Achille Mbembe, when it comes to necropolitics. We close this explanation by pointing out that there is still a lot to be done in mitigating the human suffering experienced by homeless people and that the promotion of citizenship is only possible if it is thought of jointly with all sectors of society and not only through repression